Compatibilized compositions comprising polypropylene and cyclic olefin polymers for capacitors
By combining highly isotactic propylene homopolymers, cyclic olefin polymers, and random propylene copolymers, the problem of insufficient durability of polypropylene capacitors at high temperatures is solved, and the high temperature resistance and mechanical properties are improved, making it suitable for high temperature capacitor applications.
Patent Information
- Application Number
- CN202480066615.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-20
- Filing Date
- 2024-10-18
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2044-10-18
Smart Images

Figure CN122180605B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a composition comprising 70 wt.-% to 95 wt.-% of a highly isotactic propylene homopolymer, greater than 2.5 wt.-% to less than 30 wt.-% of a cyclic olefin polymer composition, and 0.1 wt.-% to 2.5 wt.-% of a random propylene copolymer solubilizer. Furthermore, the invention relates to a membrane comprising the polypropylene composition. In addition, a biaxially oriented film comprising a polypropylene composition and a capacitor are also provided. Background Technology
[0002] Polypropylene possesses a high dielectric constant, a low dissipation factor, and good dielectric strength. Therefore, polypropylene has been successfully used as a dielectric in various capacitor film applications. However, a known problem with polypropylene capacitor grades is their limited maximum operating temperature. New generation inverters, such as traction inverters for electric vehicles and inverters for renewable energy sources (such as solar and wind power), require capacitor films with higher temperature resistance.
[0003] To date, the need for higher maximum operating temperatures, or in other words, the need for greater durability at predetermined temperature levels, has been addressed in various ways.
[0004] CN 101724195A discloses a method of compounding polypropylene with composite powdered rubber at a weight ratio of 100:0.01–100:2.0. The composite powdered rubber has a particle size of 20 nm to 100 nm and is composed of powdered silicone rubber and a nucleating agent at a weight ratio of 99:1 to 90:10. It is prepared by mixing a silicone rubber latex obtained through irradiation vulcanization with an aqueous solution or emulsion of the nucleating agent.
[0005] EP 2995641A1 teaches that high heat resistance can be achieved by compounding β-nucleated high-purity polypropylene with long-chain branched polypropylene. More specifically, it provides a polypropylene composition comprising 95.0 wt.-% to 99.9 wt.-% of a propylene homopolymer having a specific melt flow rate and very low ash content, 0.1 wt.-% to 5.0 wt.-% of long-chain branched polypropylene, and up to 1000 ppm of a β-nucleating agent.
[0006] WO 2018 / 210854A1 and WO 2018 / 197034A1 suggest that blending polypropylene with a certain amount of a specific cyclic olefin copolymer may be preferred for obtaining materials suitable for high-temperature capacitor applications. In this context, WO 2018 / 210854A1 relies on ethylene-norbornene copolymers with a specific norbornene content, while WO 2018 / 197034A1 recommends the use of cyclic olefin polymers with a wide glass transition temperature range of 120°C to 170°C.
[0007] EP 4174120A1 relates to the preparation of biaxially oriented foils from compositions comprising at least two cyclic olefin polymers and at least one semi-crystalline α-olefin polymer. The foil is characterized in that the content of all cyclic olefin polymers is in the range of 1 wt.-% to 25 wt.-% relative to the total mass of the foil. Furthermore, the glass transition temperature of the cyclic olefin polymers included in the foil is in the range of 120°C to 180°C, and the foil comprises at least a first cyclic olefin polymer and a second cyclic olefin polymer, wherein the second cyclic olefin polymer has a higher glass transition temperature than the first cyclic olefin polymer. The content of all semi-crystalline α-olefin polymers in the foil is in the range of 75 wt.-% to 99 wt.-% relative to the total mass of the foil, and the melting temperature of all semi-crystalline α-olefin polymers included in the foil is in the range of 150°C to 170°C. Furthermore, it is required that the weighted arithmetic mean of the glass transition temperatures of all cyclic olefin polymers contained in the foil is less than or equal to the weighted arithmetic mean of the crystal melting temperatures of all semi-crystalline α-olefin polymers contained in the foil.
[0008] However, in the above methods, the improved temperature resistance of the polypropylene composition for capacitors is achieved at the expense of other key properties. Mechanical properties such as low shrinkage and high stiffness, as well as the ability to withstand high voltages, are sacrificed to some extent.
[0009] Therefore, there remains a need for a polypropylene composition with an improved set of properties for capacitor applications, namely, high temperature resistance, high electrical breakdown strength, and suitable mechanical properties. Thus, one object of the present invention is to overcome the shortcomings of known compositions and to provide an improved polypropylene composition. Another object of the present invention is to provide a polypropylene film with excellent performance in capacitor applications. Last but not least, the present invention aims to provide a capacitor with improved specifications. Furthermore, the capacitor film also needs to possess high temperature resistance and good mechanical properties. Summary of the Invention
[0010] The above-mentioned objectives are achieved by a polypropylene composition having the features of independent claim 1, a film having the features of claim 10, a biaxially oriented film having the features of claim 13, and a capacitor having the features of claim 14. Other advantageous embodiments are defined in the dependent claims.
[0011] The polypropylene composition according to the invention comprises: 70 wt.-% to 95 wt.-%, preferably 74.75 wt.-% to 90 wt.-%, of a highly isotactic propylene homopolymer (A) based on the total weight of the polypropylene composition; greater than 2.5 wt.-% to less than 30 wt.-%, preferably 5 wt.-% to 25 wt.-%, of a cyclic olefin polymer composition (B) based on the total weight of the polypropylene composition; and 0.1 wt.-% to 2.5 wt.-%, preferably 0.25 wt.-% to 2 wt.-%, of a random propylene copolymer solubilizer (C) based on the total weight of the polypropylene composition. The total content of components (A) to (C) preferably reaches 100 wt.-%.
[0012] In the embodiments, the weight ratio (C) / (B) of the random propylene copolymer solubilizer (C) to the cyclic olefin polymer composition (B) ranges from 0.01 to 0.2, preferably from 0.01 to 0.1, more preferably from 0.02 to 0.075, and even more preferably from 0.02 to 0.05. When the weight ratio (C) / (B) is within this range, excellent morphological properties can be obtained. In particular, when the weight ratio (C) / (B) is within the above range, high dispersion can be achieved.
[0013] Adding a cyclic olefin polymer (B) to a highly isotactic propylene homopolymer (A) is technically advantageous because the cyclic olefin polymer composition (B) can partially compensate for the inherent increase in electrical conductivity of the highly isotactic propylene homopolymer (A) with increasing temperature. Furthermore, the combination of the cyclic olefin polymer composition (B) and the highly isotactic propylene homopolymer (A) yields favorable mechanical properties, facilitating the processing of this composition into films for capacitor applications.
[0014] In a preferred embodiment, the polypropylene composition according to the invention is obtained by melt blending a highly isotactic propylene homopolymer (A), a cyclic olefin polymer (B), and a random propylene copolymer solubilizer (C). The equipment suitable for melt blending can be selected from a group consisting of a kneader, a mill, and an extruder. Furthermore, the cyclic olefin polymer (B) itself can be obtained by melt blending at least two different cyclic olefin polymers.
[0015] Compared to dry blending, melt blending produces polypropylene compositions with high homogeneity. By selecting a cyclic olefin polymer (B) content greater than 2.5 wt% to less than 30 wt%, a random propylene copolymer solubilizer (C) content of 0.1 wt.% to 2.5 wt.%, or selecting a weight ratio (C) of random propylene copolymer solubilizer (C) to cyclic olefin polymer composition (B) ranging from 0.01 to 0.2, the cyclic olefin polymer (B) is finely and uniformly dispersed in a matrix of highly isotactic propylene homopolymer (A). Generally, the dispersion state of the cyclic olefin polymer composition is considered to influence the mechanical and electrical properties of the polypropylene composition. In other words, if the domains of the cyclic olefin polymer (B) are small, the electrical conductivity of the composition tends to decrease at high temperatures. The size and shape of the domains formed by the cyclic olefin polymer (B) in the dispersion can be analyzed using atomic force microscopy (AFM) or other types of microscopy.
[0016] Component (A) The term "homopolymer A of propylene" as used in this invention refers to polypropylene that is substantially composed of propylene units, with a propylene unit content of at least 99.5 wt.-%, more preferably at least 99.8 wt.-%. Preferably, as described in the Examples section below, by... 13 In propylene homopolymers, only propylene units can be detected by nuclear magnetic resonance (NMR) spectroscopy.
[0017] The highly isotactic propylene homopolymer (A) is preferably linear polypropylene, i.e., polypropylene without detectable amounts of long-chain or short-chain branches.
[0018] In a preferred embodiment of the present invention, the highly isotactic propylene homopolymer (A) is characterized by having a considerably high degree of isotactic regularity in its five-unit group. <mmmm>(pass 13 (Measured by C NMR). More specifically, the highly isotactic propylene homopolymer (A) can have 92% to 99.5%, preferably 93% to 99.5%, more preferably 95% to 99.0%, and even more preferably 96% to 98.5% isotactic pentad fractions. In particular embodiments, the isotactic regularity of the pentad fractions of the highly isotactic propylene homopolymer (A) is in the range of 92.0% to 94.0% or 96.0% to 98.5%, more preferably in the range of 97.0% to 98.0%.
[0019] High regularity is preferably accompanied by high crystallinity of the material. Furthermore, high regularity is preferably accompanied by low xylene cold solubles (XCS) content. Therefore, in a further preferred embodiment of the invention, the highly isotactic propylene homopolymer (A) of the present invention is characterized by a considerably low XCS content, i.e., an XCS content equal to or less than 2.0 wt.-%, more preferably equal to or less than 1.8 wt.-%, and still more preferably equal to or less than 1.6 wt.-%. Therefore, it is particularly understood that the XCS content of the highly isotactic propylene homopolymer (A) of the present invention is in the range of 0.3 wt.-% to equal to or less than 2.0 wt.-%, more preferably in the range of 0.3 wt.-% to equal to or less than 1.8 wt.-%, and still more preferably in the range of 0.4 wt.-% to equal to or less than 1.6 wt.-%.
[0020] Preferably, the XCS content refers to the XCS content determined according to ISO 16152 at 25°C. Further, the XCS content indicates that the highly isotropic propylene homopolymer (A) preferably does not contain any elastic polymer components, such as ethylene propylene rubber. In other words, the highly isotropic propylene homopolymer (A) does not correspond to multiphase polypropylene, i.e., a system consisting of a polypropylene matrix in which an elastomeric phase is dispersed. Such systems are typically characterized by a relatively high xylene cold-soluble content.
[0021] Alternatively or additionally, it is preferred that the highly isotactic propylene homopolymer (A) of the present invention has a melt flow rate within a specific range. For example, the highly isotactic propylene homopolymer has an MFR2 (230°C) measured according to ISO 1133 of 0.4 g / 10 min to 10 g / 10 min, preferably 0.5 g / 10 min to 5 g / 10 min. In a particularly preferred embodiment, the highly isotactic propylene homopolymer (A) has an MFR2 (230°C) measured according to ISO 1133 of 2.0 g / 10 min to 4.5 g / 10 min. In this context, it is well known that MFR2 (230°C) represents the melt flow rate measured at a temperature of 230°C and a load of 2.16 kg.
[0022] Furthermore, the highly isotactic propylene homopolymer (A) preferably has an ash content of 60 ppm or less, more preferably 30 ppm or less, and even more preferably 20 ppm or less. Preferably, the ash content can be in the range of 5 ppm to 30 ppm, particularly in the range of 10 ppm to 20 ppm. Low ash content is crucial for dielectric properties such as dielectric strength and dielectric loss. Ash content can be measured according to ISO 3451-1 (1997).
[0023] The highly isotactic propylene homopolymer (A) has a melting temperature Tm, as measured according to ISO 11357, in the range of 150°C to 170°C, preferably in the range of 160°C to 170°C. The crystallization temperature Tc of the highly isotactic propylene homopolymer (A), as measured according to ISO 11357, can be in the range of 110°C to 130°C, preferably in the range of 110°C to 120°C.
[0024] The highly isotactic propylene homopolymer (A) may also include one or more additives. Preferably, the content of one or more of the additives is from 0 wt.% to 2.0 wt.%, more preferably from 0.05 wt.% to 1.0 wt.%, particularly from 0.05 wt.% to 0.5 wt.%, wherein the content of each of the above additives is based on the weight of the highly isotactic propylene homopolymer (A).
[0025] One or more additives may be non-polymer additives and / or polymer additives, with non-polymer additives being preferred. For example, one or more additives may be selected from the group consisting of antioxidants, stabilizers, acid scavengers, nucleating agents, colorants, plasticizers, slip agents, antiscratch agents, dispersants, processing aids, lubricants, pigments, antistatic agents, etc. Particularly preferred is that one or more additives are selected from the group consisting of antioxidants, stabilizers, and acid scavengers, and combinations thereof.
[0026] Antioxidants and stabilizers may be selected from the hindered phenol group, and more preferably from the hindered phenol group that does not contain phosphorus or sulfur.
[0027] The antioxidant and stabilizer are particularly preferably one or more compounds selected from the group consisting of: 1,3,5-trimethyl-2,4,6-tris(3,5-di-tert-butyl-4-hydroxybenzyl)benzene (marketed under the trade names Irganox 1330, Anox 330, Ethanox 330 and Kinox-30), pentaerythritol tetrakis(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate) (marketed under the trade names Irganox 1010, Anox 20, Ethanox 310TF and Kinox-10), octadecyl 3-(3',5'-di-tert-butyl-4-hydroxyphenyl)propionate (marketed under the trade names Irganox 1076, Anox PP18 and Kinox-16), and butylated hydroxytoluene (marketed under the trade names Ionol CP and Vulkanox). BHT is sold), 1,3,5-tris(3',5'-di-tert-butyl-4'-hydroxybenzyl) isocyanurate (sold under the trade names Irganox 3114, Anox IC-14, Ethanox 314 and Kinox-34), and 3,4-dihydro-2,5,7,8-tetramethyl-2-(4,8,12-trimethyltridecyl)-2H-1-benzopyran-6-ol (sold under the trade names Irganox E 210 and α-tocopherol).
[0028] Based on the total weight of the highly isotactic propylene homopolymer (A), the total amount of antioxidants and stabilizers is preferably from 500 ppm to 8000 ppm. More preferably, based on the total weight of the highly isotactic propylene homopolymer (A), the total amount of antioxidants and stabilizers is from 800 ppm to 7000 ppm, still more preferably from 1000 ppm to 6000 ppm, and particularly from 1500 ppm to 6000 ppm. Considering the desired application of this composition in the field of capacitors, the antioxidants and stabilizers preferably do not contain phosphorus-containing auxiliary antioxidants such as tris(2,4-di-tert-butylphenyl) phosphite. Although it is not desirable to be bound by theory, the latter type of compound is considered to increase the dissipation of the final capacitor.
[0029] Acid scavengers can be salts of organic acids such as stearates. They are typically used to neutralize acids in polymers. Examples of such compounds include calcium stearate, zinc stearate, and zinc oxide. Based on the total weight of the highly isotactic propylene homopolymer (A), the amount of acid scavenger used is preferably from 20 ppm to 2000 ppm, more preferably from 50 ppm to 1000 ppm, and most preferably from 60 ppm to 600 ppm.
[0030] Therefore, one or more antioxidants and stabilizers are selected from one or more of the following groups: pentaerythritol tetrakis[3-(3',5'-di-tert-butyl-4'-hydroxyphenyl)propionate] (marketed under the trade names Irganox 1010, Anox 20, Ethanox 310TF and Kinox-10), butylated hydroxytoluene (marketed under the trade names Ionol CP and Vulkanox BHT), calcium stearate and combinations thereof.
[0031] Component (B) The cyclic olefin polymer composition (B) is preferably a thermoplastic composition.
[0032] The cyclic olefin polymer composition (B) may include or may consist substantially of a blend of one type of cyclic olefin polymer or at least two different types of cyclic olefin polymers.
[0033] It should be understood that the term "cyclic olefin polymer" refers to a polymer that includes cyclic olefin units. Cyclic olefin polymers can be cyclic olefin homopolymers or cyclic olefin copolymers.
[0034] In this invention, the term "copolymer" refers to a polymer prepared from at least two different monomers. In other words, the term "copolymer" also covers ternary copolymers and copolymers having four or more different monomer units. Therefore, a cyclic olefin polymer can be a copolymer comprising a first monomer unit (i.e., a cyclic olefin unit) and at least one second monomer unit (such as an acyclic olefin unit) different from the first monomer unit. Cyclic olefin copolymers comprising at least a first cyclic olefin unit and a second cyclic olefin unit different from the first cyclic olefin unit are also covered by the term "cyclic olefin polymer".
[0035] Cyclic olefin copolymers can be random cyclic olefin copolymers or cyclic olefin block copolymers (CBCs). Cyclic olefin block copolymers can be obtained by anionic polymerization of styrene and a conjugated diene (such as butadiene) and can be obtained by selecting a subsequent hydrogenation step. Therefore, in a preferred embodiment, the cyclic olefin block copolymer can be a fully hydrogenated styrene-butadiene block copolymer. Such cyclic olefin block copolymers are, for example, commercially available products from Taiwan Polymer Chemicals Co., Ltd. (USI). The use of cyclic olefin block copolymers has advantages from the perspective of facilitating subsequent processing. For example, it is anticipated that only a machine direction (MD) to transverse (TD) draw ratio of 2.0 to 4.0 times is required to produce oriented films from polypropylene compositions comprising one or more cyclic olefin block copolymers as cyclic olefin polymer compositions (B).
[0036] Cyclic olefin polymers can also be obtained by ring-opening polymerization or ring-retention polymerization of at least one cyclic olefin monomer. Among these alternatives, ring-retention polymerization is preferred for obtaining cyclic olefin polymers.
[0037] In a further preferred embodiment, at least one cyclic olefin monomer is selected from the group consisting of cyclopentadiene, tetracyclododecene, norbornene, styrene, and derivatives of the above compounds. Norbornene and its derivatives are particularly preferred examples of at least one cyclic olefin monomer.
[0038] Norbornene and its derivatives are preferably compounds according to formula (I).
[0039] Where n is 0 or 1, m is 0 or an integer, specifically 0 or 1. R 1 R 2 R 3 R 4 R 5 and R 6 Independently selected from the group consisting of hydrogen, halogen, alkyl, cycloalkyl, aryl, and alkoxy groups. R 7 R 8 R 9 R 10 R 11 R 12 R 13 R 14 R 15 and R 16 Independently selected from the group consisting of hydrogen and alkyl groups, R 17 R 18 R 19 and R 20 Independently selected from the group consisting of hydrogen, halogen, alkyl, cycloalkyl, and aryl, wherein R 17 and R 19 Alternatively, cyclic rings or cyclic systems can be formed, which may be saturated or unsaturated.
[0040] Further and equally preferably, an example of a norbornene derivative is a compound according to formula (II).
[0041] Among them, R 21 and R 22 Independently selected from the group consisting of hydrogen, C5-C7 cycloalkyl, C5-C7 aryl, and C1-C4 alkyl, and R 23 and R 24 The group consisting of hydrogen and C1-C4 alkyl groups is selected independently.
[0042] The acyclic olefin monomer can be an α-olefin and / or a conjugated diene. Non-limiting examples of α-olefins are C2-C8 α-olefins, such as those selected from the group consisting of ethylene, propylene, 1-butene, 2-methyl-1-propene (isobutene), and 3-methyl-1-butene. Preferred α-olefins are straight-chain C2-C8 α-olefins such as ethylene and propylene. Particularly preferred is butadiene as the conjugated diene.
[0043] In one embodiment, the cyclic olefin polymer composition (B) comprises at least one cyclic olefin copolymer selected from the group consisting of norbornene-ethylene copolymer and tetracyclododecene-ethylene copolymer, or blends of at least two of said cyclic olefin copolymers. In a particularly preferred embodiment, the cyclic olefin polymer composition (B) comprises or substantially consists of a norbornene-ethylene copolymer or a blend of two norbornene-ethylene copolymers having different norbornene contents. Furthermore, non-limiting examples of cyclic olefin polymers are polymers commercially available from Mitsui Chemicals under APEL® or from TOPAS Advanced Polymers under TOPAS®.
[0044] The glass transition temperature (hereinafter also referred to as "Tg") of the cyclic olefin polymer composition (B) can be controlled by the type of monomers used, for example by the type of at least one cyclic olefin monomer, and optionally, if present, by the type of a noncyclic olefin monomer. If the cyclic olefin polymer composition (B) is a blend of at least two cyclic olefin polymers, the weight ratio of the cyclic olefin polymers also affects the glass transition temperature of the composition. Furthermore, in the case where the cyclic olefin polymer composition is a composition comprising at least one cyclic olefin copolymer, the amount of cyclic olefin monomer can be used to adjust the overall glass transition temperature of the composition. For norbornene-ethylene copolymers, for example, it is known that a higher glass transition temperature can be achieved by increasing the norbornene content. This also applies to other combinations of cyclic olefin monomers and noncyclic olefin monomers.
[0045] The cyclic olefin polymer composition (B) may include cyclic olefin units (e.g., norbornene units) and noncyclic olefin units (e.g., ethylene units), wherein the content of the cyclic olefin units is 70 wt.-% to 90 wt.-%, preferably 75 wt.-% to 85 wt.-%, more preferably 75 wt.-% to 80 wt.-%, and the content of the noncyclic olefin units is 10 wt.-% to 30 wt.-%, preferably 15 wt.-% to 25 wt.-%, more preferably 20 wt.-% to 25 wt.-%, wherein each content is based on the total weight of the cyclic olefin polymer composition (B). If the cyclic olefin polymer composition (B) is soluble, the content of the cyclic olefin units in the cyclic olefin polymer composition (B) can be measured by 13C NMR spectroscopy; if the cyclic olefin polymer composition (B) is insoluble, the content of the cyclic olefin polymer composition (B) can be calculated based on the glass transition temperature of the cyclic olefin polymer. If the cyclic olefin polymer (B) is a norbornene-ethylene copolymer and the cyclic olefin unit is a norbornene unit, its content can be measured as described in Macromol. Chem. Phys. 199, 1221-1232 (1998).
[0046] In a preferred embodiment, the cyclic olefin polymer composition (B) may have a glass transition temperature measured according to ISO 11357-3, which may be in the range of 130°C to 160°C. In another preferred embodiment, the cyclic olefin polymer composition (B) may have a glass transition temperature measured according to ISO 11357-3, which may be in the range of 140°C to 155°C.
[0047] Additionally or alternatively, the cyclic olefin polymer composition (B) preferably has an MFR2 (260°C, 2.16 kg) measured according to ISO 1133 of 2 g / 10 min to 50 g / 10 min, more preferably 8 g / 10 min to 25 g / 10 min.
[0048] In a particularly preferred embodiment, the cyclic olefin polymer composition (B) comprises or is primarily composed of at least a first cyclic olefin polymer (b1) and a second cyclic olefin polymer (b2). The first cyclic olefin polymer (b1) has a glass transition temperature, as measured according to ISO 11357, below 140°C, such as 60°C to below 140°C, for example, 100°C to below 140°C. The second cyclic olefin polymer (b2) preferably has a glass transition temperature, as measured according to ISO 11357, of at least 155°C, particularly at least 155°C to 190°C. The first and second cyclic olefin polymers can be melt-blended to form the cyclic olefin polymer composition, preferably in a weight ratio of 1:5 to 5:1, particularly in a weight ratio of 1:3 to 3:1.
[0049] Using two cyclic olefin polymers with different glass transition temperatures (TVTs) would result in a wider glass transition temperature range for the polypropylene composition, thus extending its processing window. Furthermore, using two cyclic olefin polymers with different TVTs allows for better control over the material's high-temperature properties.
[0050] Component (C) In a preferred embodiment, the random propylene copolymer solubilizer (C) has an MFR2 (2.16 kg / 230 °C) of 1.0 g / 10 min to 100 g / 10 min as measured according to ISO 1133, preferably 1.5 g / 10 min to 75 g / 10 min, and more preferably 2.0 g / 10 min to 50 g / 10 min.
[0051] Furthermore, the random propylene copolymer solubilizer (C) has a melt temperature of 150°C or lower, preferably less than 150.0°C, more preferably greater than 130.0°C to less than 150.0°C, and most preferably greater than 140.0°C to less than 149.0°C, as measured according to ISO 11357-3, with heating and cooling rates of 10 K / min.
[0052] Additionally or alternatively, the atactic propylene copolymer solubilizer (C) may have an ethylene content of 0.5 wt.-% to 8.0 wt.-%, preferably 1.0 wt.-% to 4.0 wt.-%, more preferably 2.0 wt.-% to 3.8 wt.-%. The ethylene content of the atactic propylene copolymer solubilizer (C) can be measured by NMR.
[0053] The random propylene copolymer solubilizer (C) may include one or more additives. Preferably, the content of one or more additives is from 0 wt.-% to 2.0 wt.-%, more preferably from 0.05 wt.-% to 1.0 wt.-%, particularly from 0.05 wt.-% to 0.5 wt.-%, wherein the content of each of the above additives is based on the weight of the random propylene copolymer solubilizer (C).
[0054] One or more additives may be non-polymer additives and / or polymer additives, with non-polymer additives being preferred. For example, one or more additives may be selected from the group consisting of antioxidants, stabilizers, acid scavengers, nucleating agents, colorants, plasticizers, slip agents, antiscratch agents, dispersants, processing aids, lubricants, pigments, antistatic agents, etc. Particularly preferred are one or more additives selected from the group consisting of antioxidants, stabilizers, and acid scavengers, and combinations thereof. Examples of suitable additive compounds have been described in the context of component (A) above.
[0055] Suitable conditions for the manufacture of component (C) are described in particular in WO 2014 / 187686A1 and WO 2014 / 187687A1.
[0056] The component (C) according to the invention can be produced by a continuous polymerization process in the presence of a Ziegler-Natta catalyst as defined below.
[0057] Therefore, preferably, component (C) is generated in the presence of (a) a Ziegler-Natta catalyst (ZN-C), preferably comprising a titanium compound (TC), a magnesium compound (MC) and an internal donor (ID), wherein the internal donor (ID) is preferably a non-phthalate, (b) optionally a co-catalyst (Co) and (c) optionally an external donor (ED).
[0058] Component (C) can be generated in a continuous polymerization process comprising at least two reactors (R1) and (R2), wherein a first propylene copolymer component (R-PP1) is generated in the first reactor (R1) and then transferred to the second reactor (R2), wherein a second propylene copolymer component (R-PP2) is generated in the second reactor (R2) in the presence of the first propylene copolymer component (R-PP1).
[0059] The term "continuous polymerization system" refers to the generation of propylene copolymer (R-PP) in at least two reactors connected in series. Therefore, this polymerization system includes at least a first polymerization reactor (R1) and a second polymerization reactor (R2), and optionally a third polymerization reactor (R3). The term "polymerization reactor" refers to the site where the main polymerization reaction occurs. Therefore, in the case where the process consists of two polymerization reactors, this definition does not exclude the inclusion of a prepolymerization step, for example, in a prepolymerization reactor. The term "consisting of" is only a closed-ended expression for the main polymerization reactor. Preferably, at least one of the two polymerization reactors (R1) and (R2) is a gas-phase reactor (GPR). More preferably, the second polymerization reactor (R2) and the optional third polymerization reactor (R3) are gas-phase reactors (GPRs), namely the first gas-phase reactor (GPR1) and the second gas-phase reactor (GPR2). According to the invention, the gas-phase reactor (GPR) is preferably a fluidized bed reactor, a fast fluidized bed reactor, or a fixed bed reactor, or a combination thereof.
[0060] A preferred multi-stage process is the loop-vapor phase process, such as the Borstar® technology developed by Borealis A / S, Denmark, which is described in patent documents such as EP0887379Al, WO 92 / 12182Al, WO 2004 / 000899Al, WO 2004 / 111095Al, WO 99 / 24478Al, WO 99 / 24479Al, or WO 00 / 68315Al. Another suitable loop-vapor phase process is the Spheripol® process from Basell.
[0061] The process for manufacturing component (C) may include steps under the following conditions: (a) In a first polymerization reactor (R1), i.e., a loop reactor (loop), propylene is polymerized with ethylene and / or comonomers of C4 to C12 α-olefins, preferably propylene and ethylene, to obtain a first propylene copolymer portion (R-PP1) of propylene copolymer (R-PP); (b) the first propylene copolymer portion (R-PP1) is transferred to a second polymerization reactor (R2); (c) in the second polymerization reactor (R2), in the presence of the first propylene copolymer portion (R-PP1), propylene is polymerized with ethylene and / or comonomers of C4 to C12 α-olefins, preferably propylene and ethylene, to obtain a second propylene copolymer portion (R-PP2) of propylene copolymer (R-PP); the first propylene copolymer portion (R-PP1) and the second propylene copolymer portion (R-PP2) constitute the propylene copolymer (R-PP).
[0062] The prepolymerization described above can be performed before step (a).
[0063] As noted above, the Ziegler-Natta catalyst (ZN-C) is preferably used in the specific process for preparing component (C). Therefore, the Ziegler-Natta catalyst (ZN-C) will be described in more detail below.
[0064] The catalyst that can be used to prepare component (C) is preferably a solid Ziegler-Natta catalyst (ZN-C), which comprises a titanium compound (TC), a magnesium compound (MC), and an internal donor (ID), wherein the internal donor (ID) is a non-phthalic acid ester, most preferably a non-phthalic acid dicarboxylic acid diester. Therefore, the catalyst used in this invention is completely free of unwanted phthalic acid compounds. The Ziegler-Natta catalyst (ZN-C) can also be further defined by its acquisition method. Therefore, the Ziegler-Natta catalyst (ZN-C) is preferably obtained by a process comprising the following steps: a) providing a solution of at least one complex, which is a complex of a magnesium compound (MC) and an alcohol, wherein the alcohol includes at least one oxygen-containing group other than a hydroxyl group, and optionally, the at least one complex is a complex of a magnesium compound (MC) and an alcohol, wherein the alcohol does not include any other oxygen-containing groups; b) combining the solution with a titanium compound (TC) to generate an emulsion in which the magnesium content in the dispersed phase exceeds 50 mol%; c) stirring the emulsion so that the average size of the dispersed phase droplets is preferably maintained in the range of 5 µm to 200 µm; d) solidifying the dispersed phase droplets; e) recovering the solidified particles of the olefin polymerization catalyst component, wherein an internal donor (ID) is added in any step prior to step c), and the internal donor (ID) is a non-phthalate, preferably a non-phthalic acid dicarboxylic acid diester.
[0065] A detailed description of how to obtain such a Ziegler-Natta catalyst (ZN-C) is disclosed in WO 2012 / 007430A1.
[0066] membrane The present invention also provides a film comprising the polypropylene composition described above. The film may be a compression-molded film. In this case, the film can be produced by a mold at a temperature ranging from 190°C to 230°C, the mold having a thickness of 10 μm to 300 μm, preferably 10 μm to 100 μm, more preferably 20 μm to 80 μm, and particularly 60 μm. Alternatively, the film may be a cast film. Optionally, the mold may be a biaxially oriented (BOPP) film. In particular, the film may be a cast film that has undergone biaxial orientation (BOPP).
[0067] The thickness of the membrane is preferably from 1µm to 1000µm, more preferably from 1µm to 300µm, most preferably from 1µm to 250µm, and particularly from 1µm to 100µm. This is especially advantageous because the current trend is to provide electrical systems with higher energy density and efficiency. Reducing the space occupied by the membrane in the membrane capacitor helps to achieve this goal.
[0068] If a cast film with a thickness of 100 µm is provided, the film preferably has an electrical conductivity of less than 6.0 × 10⁻⁶. -15 S / cm, preferably below 3.0·10 -16 S / cm, more preferably greater than 3.0·10 -17 S / cm to below 3.0·10 -16 The conductivity is within the range of S / cm, where the conductivity is obtained by dielectric impedance spectroscopy at 130°C using 10... -2 The AC current is measured at a frequency of Hz.
[0069] Furthermore, atomic force microscopy was used to examine the 10 × 10 μm thickness of a 300 μm film. 2 Visual inspection of the slices determined that the average diameter of the domains of the cyclic olefin polymer composition (B) was less than 2.0 μm, preferably in the range of 0.1 μm to 2.0 μm, and more preferably in the range of 0.2 μm to 1.0 μm. The average diameter may be determined based on the evaluation of more than 30 samples.
[0070] The biaxially oriented polypropylene film according to the present invention can be obtained through two steps. First, a non-oriented film is generated by extruding a polypropylene composition using a flat die. Second, the non-oriented film is stretched in both the machine direction (MD) and transverse direction (TD). The stretching or orientation of the non-oriented film can be performed simultaneously in both the machine direction and transverse direction. The two steps of this method are preferably carried out in a continuous process. Alternatively, the non-oriented film can be collected and cooled with rotating cooling rollers to cure the film before stretching.
[0071] In one embodiment, the biaxially oriented polypropylene film comprises at least 80 wt.-%, more preferably at least 90 wt.-%, and still more preferably a polypropylene composition as defined in this invention. Preferably, the biaxially oriented polypropylene film has a stretch ratio in the machine direction of at least 2.5 times, more preferably at least 3.0 times, more preferably 4 times, particularly at least 5 times, and a stretch ratio in the transverse direction of at least 4 times, preferably at least 5 times; more preferably, the biaxially oriented polypropylene film has a stretch ratio in the machine direction of at least 9 times and a stretch ratio in the transverse direction of at least 5 times.
[0072] Biaxially oriented polypropylene films can be prepared using conventional stretching processes known in the art. Therefore, the process for manufacturing biaxially oriented polypropylene films preferably employs the tender method known in the art.
[0073] Tensor stretching is a method of melt-extruding a polypropylene composition as defined herein from a slot die (such as a T-die) and cooling it on a cooling drum to obtain a non-oriented film. The film is preheated, for example, by heated metal rollers, and then stretched lengthwise between multiple rollers with a circumferential speed difference established between them. The two edges of the film are then clamped and stretched laterally in an oven using a tenter frame to obtain a biaxially oriented film. Thus, the temperature of the film during longitudinal stretching is preferably controlled within the temperature range of the melting point of the polypropylene composition.
[0074] Subsequently, the biaxially oriented film can be subjected to corona discharge treatment in air, nitrogen, carbon dioxide gas, or any mixture thereof. If metallization of the film is required for use in membrane capacitor applications, this can enhance its adhesion strength to the metal to be deposited.
[0075] capacitor On the other hand, the present invention relates to a capacitor comprising a biaxially oriented film as described above. Capacitors comprising biaxially oriented films are expected to have a longer lifespan and higher temperature resistance than conventional capacitors. Preferably, the biaxially oriented film is metallized, and the capacitor is a metallized film capacitor. Metallization of the biaxially oriented film can be performed by any process known in the art, such as evaporation, electrodeposition, melting, ion beam vacuum deposition, sputtering, or ion plating. The thickness of the resulting metal layer can range from 100 Å (0.01 µm) to 5000 Å (0.5 µm).
[0076] Alternative polypropylene compositions In a second alternative aspect, a polypropylene composition is provided comprising a highly isotactic propylene homopolymer (A), a cyclic olefin polymer composition (B), and a random propylene copolymer solubilizer (C), wherein the content of the highly isotactic propylene homopolymer (A) is 70 wt% or more based on the total weight of the polypropylene composition, and the weight ratio (C) / (B) of the random propylene copolymer solubilizer (C) to the cyclic olefin polymer composition (B) ranges from 0.01 to 0.2, provided that the sum of the contents of components (A) to (C) is 100 wt%.
[0077] The polypropylene composition according to the second aspect can also be processed into a film (oriented or non-oriented) in the same manner as the aforementioned polypropylene composition.
[0078] According to the second aspect, the polypropylene composition can also be used to prepare capacitors comprising biaxially oriented films. Furthermore, the preferred characteristics of components (A)-(C) described above also apply to the polypropylene composition. Attached Figure Description
[0079] The embodiments of the present invention are illustrated by way of example and are not limited to the figures in the accompanying drawings.
[0080] Figures 1 to 7 An atomic force microscopy image of an exemplary non-oriented film composed of polypropylene compositions CEI and IE1-IE6 is shown. Detailed Implementation
[0081] Measurement methods Quantification of C2 content using NMR spectroscopy
[0082] Quantized NMR spectroscopy was used to quantify the comonomer content of the polymer. (This is for...) 1 H and 13 The quantitative analysis of the solution state was recorded using a Bruker Advance III 400 NMR spectrometer operating at 400.15 MHz and 100.62 MHz, respectively. 13 C{ 1 ¹H NMR spectroscopy. Using nitrogen gas in all pneumatic devices. 13 The C-optimized 10mm extended temperature probe recorded all spectra at 125°C.
[0083] Approximately 200 mg of the material was dissolved in 3 mL of 1,2-tetrachloroethane-d2 (TCE-d2) with the addition of chromium acetylacetone (Cr(acac)3) to obtain a solution with a 65 mM relaxant solvent (Singh, G., Kothari, A., Gupta, V., Polymer Testing 28 5 (2009), 475). To ensure a homogeneous solution, after initial sample preparation in the heating zone, the NMR tube was further heated in a rotary furnace for at least 1 hour. The tube was then rotated at a frequency of 10 Hz with a magnet inserted. This setup was chosen primarily for high resolution and the precise ethylene content required for quantitative analysis. Standard single-pulse excitations, which do not utilize the nuclear Oferhauser effect (NOE), were achieved using an optimized flip angle, a 1-second cyclic delay, and a dual-level WALTZ16 decoupling scheme (Zhou, Z., Kuemmerle, R., Qiu, X., Redwine, D., Cong, R., Taha, A., Baugh, D.Winniford, B., J.Mag.Reson.187(2007) 225; Busico, V.,Carbonniere, P., Cipullo, R., Pellecchia, R., Severn, J., Talarico, G.,Macromol. Rapid Commun. 2007, 28, 1128). A total of 6144 (6k) transients were obtained for each spectrum. Quantization was performed using a proprietary computer program. 13 C{ 1 The ¹H NMR spectra were processed, integrated, and the relevant quantitative properties were determined based on the integration. All chemical shifts were calculated using the solvent chemical shifts, indirectly referencing the central methylene group of the ethylene block (EEE) at 30.00 ppm. This method allows for comparable references even in the absence of this structural unit. Characteristic signals corresponding to ethylene incorporation were also observed (Cheng, HN, Macromolecules 17 (1984), 1950).
[0084] The method of Wang et al. (Wang, WJ., Zhu, S., Macromolecules 33 (2000), 1157) was adopted to quantify the comonomer fraction by integrating multiple signals across the entire spectral region of the 13C{1H} NMR spectrum. This method was chosen for its robustness and ability to account for regional defects when necessary. The integration region was fine-tuned to improve its applicability across the entire range of comonomer content encountered.
[0085] For systems where isolated ethylene is observed only in the PPEPP sequence, the method of Wang et al. was modified to reduce the influence of non-zero integrals at known non-existent sites. By reducing the number of sites used to determine the absolute ethylene content, this method reduces the overestimation of ethylene content in such systems.
[0086] E = 0.5 (Sββ + Sβγ + Sβδ + 0.5 (Sαβ + Sαγ))
[0087] The ethylene blending amount (molar percentage) is calculated as follows:
[0088] The ethylene blending amount (weight percentage) is calculated from the mole fraction as follows:
[0089] Quantification of regularity using NMR spectroscopy The isotactic regularity of polymers is quantified using nuclear magnetic resonance (NMR) spectroscopy.
[0090] Use for 1 H and 13 The quantitative analysis of the solution state was recorded using a Bruker Advance III 400 NMR spectrometer operating at 400.15 MHz and 100.62 MHz, respectively. 13 C1H NMR spectroscopy. Using nitrogen gas in all pneumatic devices. 13 The C-optimized 10mm extended temperature probe recorded all spectra at 125°C.
[0091] For the polypropylene homopolymer, approximately 200 mg of material was dissolved in 1,2-tetrachloroethane-d2 (TCE-d2). To ensure a homogeneous solution, after initial sample preparation in the heating zone, the NMR tube was further heated in a rotary furnace for at least 1 hour. The tube was then rotated at a frequency of 10 Hz after being inserted into a magnet. This setup was chosen primarily for the high resolution required for quantifying the stereoregularity distribution (Busico, V., Cipullo, R., Prog.Polym.Sci.26(2001) 443;Busico, V.; Cipullo, R., Monaco, G., Vacatello, M., Segre, AL, Macromoleucles 30(1997) 6251). Standard single-pulse excitation was achieved using a NOE and a dual-level WALTZ16 decoupling scheme (Zhou, Z., Kuemmerle, R., Qiu, X., Redwine, D., Cong, R., Taha, A., Baugh, D.Winniford, B., J.Mag.Reson.187(2007)225; Busico, V., Carbonniere, P., Cipullo, R., Pellecchia, R., Severn, J., Talarico, G., Macromol. RapidCommun.2007, 28, 11289). A total of 8192 (8k) transients were obtained for each spectrum.
[0092] Quantization using proprietary computer programs 13 C{ 1 The H NMR spectra are processed, integrated, and the relevant quantization properties are determined based on the integration.
[0093] For polypropylene homopolymers, all chemical shifts are intrinsically referenced to the methyl isotactic pentamematic group at 21.85 ppm. <mmmm>.
[0094] Observe the characteristic signals corresponding to regional defects (Resconi, L., Cavallo, L., Fait, A., Piemontesi, F., Chem.Rev.2000, 100, 1253; Wang, WJ., Zhu, S., Macromolecules33(2000), 1157; Cheng, HN, Macromolecules 17(1984), 1950) or the characteristic signals of comonomers.
[0095] Stereoregularity distribution was quantified by integrating the methyl region between 23.6 ppm and 19.7 ppm, correcting for any sites unrelated to the stereo sequence of interest (Busico, V., Cipullo, R., Prog.Polym.Sci.26(2001) 443; Busico, V., Cipullo, R., Monaco, G., Vacatello, M., Segre, AL,Macromolecules 30 (1997) 6251).
[0096] Specifically, the influence of regional defects and comonomers on the quantification of stereoregularity distribution is corrected by subtracting representative regional defects and comonomer integrals from specific integral regions of the stereo sequence.
[0097] Isothetic regularity was determined at the quintet level and reported as the percentage of isothetic quintet (mmmm) sequences relative to all quintet sequences:
[0098] Melt Flow Rate MFR2 MFR2 is measured according to ISO 1133 (at a load of 2.16 kg) at a temperature of 230 °C (for highly isotactic propylene homopolymers) or 260 °C (for cyclic olefin copolymers).
[0099] XCS content XCS content is measured according to ISO 16152 and expressed as a weight percentage, as follows: Dissolve 2.0 g of the sample in 250 mL of p-xylene and stir at 135 °C. After 30 minutes, cool the solution at room temperature for 15 minutes, then let it stand at 25 ± 0.5 °C for 30 minutes. Filter the solution through filter paper into two 100 mL flasks. Evaporate the solution in the first 100 mL flask under a nitrogen stream and dry the residue under vacuum at 90 °C to constant weight. Then, determine the xylene-soluble fraction (weight percentage) as follows:
[0100] Where, m o =Initial polymer amount (g); m =Residual weight (g); V0 =Initial volume (ml); v =Volume of analytical sample (mL)
[0101] Glass transition temperature Tg The glass transition temperature was measured using a differential scanning calorimeter at a scan rate of 10 K / min according to ISO 11357.
[0102] Melting temperature Tm, crystallization temperature Tc Differential scanning calorimetry (DSC) experiments were performed on a TA Instruments Q2000 instrument calibrated with indium, zinc, and tin according to ISO 11357 / 1. Measurements were taken under a nitrogen atmosphere (50 mL / min). -1 The measurements were performed at -30°C to 225°C using a scan rate of 10 K / min in heating / cooling / heating cycles, according to ISO 11357 / 3. The peak values of the endothermic and exothermic peaks in the cooling and second heating cycles were taken as the melting temperature Tm and crystallization temperature Tc, respectively.
[0103] Ash content The ash content of the polymer was determined according to ISO 3451-1 (1997). The procedure was as follows: approximately 100 g of polymer was weighed and placed in a platinum crucible. The crucible was then heated over a Bunsen burner flame, allowing the polymer to slowly ignite. After complete ignition, the crucible was cooled, dried, and weighed. The ash content was calculated by dividing the weight of the residue by the weight of the polymer sample. At least two measurements were performed; if the difference between the two measurements exceeded 7 ppm, a third measurement was performed.
[0104] Morphological properties Non-oriented film samples with a thickness of 300 μm were prepared from a polypropylene composition and cut at the core of the film using a cryostat in a direction perpendicular to the machine direction (MD). No surface treatment was performed.
[0105] The size of the domain formed by component (B) was analyzed using atomic force microscopy (AFM).
[0106] In addition to the "conventional" scan, a qualitative amplitude-frequency modulation (AM-FM) scan was performed because the latter can better distinguish different phases. A large surface area image of 10 × 10 μm² based on the membrane was then used for comparison.
[0107] Electrical properties A 100 μm thick non-oriented film sample was prepared from a polypropylene composition and cut using a cryostat along the core perpendicular to the machine direction (MD). No surface treatment was performed.
[0108] Electrical properties were evaluated using dielectric spectroscopy (DS) measurements. These measurements were performed using a Novocontrol Alpha frequency analyzer at different temperature ranges of 80°C to 150°C or 80°C to 160°C and at atmospheric pressure. The frequency range of the DS measurements was 0.01 Hz. The film sample was placed between two identical electrodes with a diameter of 40 mm. The measurements were performed under a nitrogen atmosphere.
[0109] Material Components (A) and (B) The polymers listed in Table 1 below have been used to prepare example materials.
[0110] Table 1: Polymers used to generate CE1 and IE1-IE6
[0111] Component (C) In addition, component (C) was obtained according to the following description and has been used to prepare example materials.
[0112] C1-C3 is a random copolymer of polypropylene, and its preparation process involves a continuous process of a prepolymer reactor, a loop reactor, and a gas phase reactor (GPR1).
[0113] The catalyst used in the polymerization reaction to produce Cl-C3 is prepared as follows: Preparation of magnesium alkoxy compounds 3.4 L of 2-ethylhexanol and 810 mL of propylene glycol butyl monoether (molar ratio 4 / 1) were added to a 20 L reactor. Then, 7.8 L of a 20% butyl ethyl magnesium (BEM) toluene solution was slowly added to the well-stirred alcohol mixture. The temperature was maintained at 10 °C during the addition. After the addition was complete, the temperature of the reaction mixture was raised to 60 °C and stirred at this temperature for 30 minutes. Finally, after cooling to room temperature, the obtained magnesium alkoxide was transferred to a storage container.
[0114] The 21.2 g magnesium alkoxide prepared above was mixed with 4.0 mL of diisooctyl citrate for 5 minutes. After mixing, the resulting magnesium complex was immediately used to prepare the catalyst component.
[0115] Preparation of solid catalyst components 19.5 mL of titanium tetrachloride was placed in a 300 mL reactor equipped with a mechanical stirrer at 25 °C. The stirring speed was adjusted to 170 rpm. 26.0 g of the magnesium complex prepared above was added over 30 minutes at 25 °C. 3.0 mL of Viscoplex 1-254 and 1.0 mL of toluene solution containing 2 mg Necadd 447 were added. Then, 24.0 mL of heptane was added to form an emulsion. Stirring was continued at 25 °C for 30 minutes. The reactor temperature was then raised to 90 °C over 30 minutes. The reaction mixture was stirred at 90 °C for another 30 minutes. Stirring was then stopped, and the reaction mixture was allowed to stand at 90 °C for 15 minutes.
[0116] washing The solid material was washed five times: each wash was performed by stirring at 80°C for 30 minutes at a speed of 170 rpm. After stirring was stopped, the reaction mixture was allowed to stand for 20-30 minutes, and then siphoned.
[0117] Wash 1: Wash with 100 mL of toluene and 1 mL of donor mixture.
[0118] Washing 2: Wash with 30 mL TiCl4 and 1 mL donor mixture.
[0119] Washing 3: Wash with 100 mL of toluene.
[0120] Washing 4: Wash with 60 mL of heptane.
[0121] Washing 5: Wash with 60 mL of heptane and stir for 10 minutes. Then stop stirring, let the reaction mixture stand for 10 minutes, lower the temperature to 70°C, then siphon, and then purge with nitrogen for 20 minutes to generate an air-sensitive powder.
[0122] Catalysts for component (C) polymerization Table 2 lists the molar ratio of cocatalyst (Co) to external donor (ED) [Co / ED] and the molar ratio of cocatalyst (Co) to titanium compound (TC) [Co / TC]. Polymerization conditions are also listed in Table 2.
[0123] In addition to the polymerization conditions in Table 2, C1 was viscosified using a co-rotating twin-screw extruder at 200℃-230℃. An appropriate amount of 2,5-bis(tert-butyl)-2,5-dimethylhexane (Trigonox 101, distributed by Akzo Nobel, Netherlands) was used to achieve a target MFR2 of 8 g / 10 min.
[0124] Table 2: Polymerization conditions for preparing solubilizers C1-C3 ;
[0125] Polypropylene composition The above materials are mixed in the proportions listed in Table 3 to obtain a polypropylene composition.
[0126] Table 3: Comparison of the polypropylene compositions IE1-IE6 (compensated) and CE1 (non-compensated) of the present invention
[0127] membrane Polypropylene compositions IE1-IE6 and CE1 were compressed into films using a 60 μm thick mold. The electrical properties of the non-oriented compression-molded films (approximately 100 μm thick after demolding) were measured according to the above method. The morphological properties of a 300 μm thick non-oriented film (also referred to as a 300 μm sheet) made from polypropylene compositions IE1-IE6 and CE1 were measured according to the above method. The measurement results are shown in Table 4 below.
[0128] In particular, to obtain the average diameter of the domains of component (B), all (B)-domains visible in the AFM images were analyzed. The diameter of each domain was measured manually, and the values reported in Table 4 are the average of the diameters of all domains.
[0129] Table 4: Comparison of morphological and electrical properties of CE1 and IE1-IE6
[0130] also, Figure 1-7 AFM images of the membranes of compositions CE1 and 1E1-1E6 are also shown, demonstrating that the membranes of compositions IE1-IE6 of the present invention achieve a finer dispersed phase of component (B).
[0131] It can be seen that, at temperatures above 100°C, the conductivity of the membranes IE2, IE3, IE5, and IE6 of the present invention is improved compared to the comparative membrane CE1.< / mmmm> < / mmmm>
Claims
1. A polypropylene composition, characterized in that, include: Based on 70 wt.-% to 95 wt.-% of the total weight of the polypropylene composition, of highly isotactic propylene homopolymer (A). Based on the total weight of the polypropylene composition, a cyclic olefin polymer composition (B) of greater than 2.5 wt.% to less than 30 wt.% is present, and The random propylene copolymer solubilizer (C) is 0.1 wt.-% to 2.5 wt.-% of the total weight of the polypropylene composition.
2. The polypropylene composition according to claim 1, characterized in that, The weight ratio (C) / (B) of the random propylene copolymer solubilizer (C) to the cyclic olefin polymer composition (B) ranges from 0.01 to 0.
2.
3. The polypropylene composition according to claim 1, characterized in that, The weight ratio (C) / (B) of the random propylene copolymer solubilizer (C) to the cyclic olefin polymer composition (B) ranges from 0.01 to 0.
075.
4. The polypropylene composition according to claim 1, characterized in that, The random propylene copolymer solubilizer (C) has a melt flow rate (MFR2) of 1.0 g / 10 min to 100 g / 10 min as measured according to ISO 1133 (2.16 kg / 230°C).
5. The polypropylene composition according to claim 1, characterized in that, The random propylene copolymer solubilizer (C) has a melt flow rate (MFR2) of 2.0 g / 10 min to 50 g / 10 min as measured according to ISO 1133 (2.16 kg / 230°C).
6. The polypropylene composition according to claim 1, characterized in that, The random propylene copolymer solubilizer (C) has at least one of the following characteristics: The melting point, as measured according to ISO 11357-3, is 150°C or less, and The ethylene content, measured by nuclear magnetic resonance, ranged from 0.5 wt.% to 8.0 wt.%.
7. The polypropylene composition according to claim 1, characterized in that, The random propylene copolymer solubilizer (C) is obtained by polymerizing propylene and ethylene and / or C4 to C4 in the presence of C4. 12 Obtained from α-olefin comonomers: Ziegler-Natta catalyst.
8. The polypropylene composition according to claim 1, characterized in that, The random propylene copolymer solubilizer (C) is obtained by polymerizing propylene and ethylene and / or C4 to C4 in the presence of C4. 12 Obtained from α-olefin comonomers: Ziegler-Natta catalyst, wherein the Ziegler-Natta catalyst comprises a titanium compound, a magnesium compound, and an internal donor.
9. The polypropylene composition according to claim 1, characterized in that, The cyclic olefin polymer composition (B) has at least one of the following characteristics: The glass transition temperature, as measured according to ISO 11357-3, is in the range of 130°C to 160°C. The melt flow rate (MFR2) (2.16 kg / 260 °C) measured according to ISO 1133 is 2 g / 10 min to 50 g / 10 min.
10. The polypropylene composition according to claim 1, characterized in that, The cyclic olefin polymer composition (B) has at least one of the following characteristics: The glass transition temperature, as measured according to ISO 11357-3, is in the range of 140°C to 155°C. The melt flow rate (MFR2) (2.16 kg / 260 °C) measured according to ISO 1133 is 8 g / 10 min to 25 g / 10 min.
11. The polypropylene composition according to claim 1, characterized in that, The cyclic olefin polymer composition (B) is a cyclic olefin copolymer composition, which comprises: Cycloolefin units, in a content of 70 wt.-% to 90 wt.-%, and Acyclic olefin units, in a content of 10 wt.-% to 30 wt.-%. The contents are all based on the total weight of the cyclic olefin polymer composition (B).
12. The polypropylene composition according to claim 1, characterized in that, The cyclic olefin polymer composition (B) is a cyclic olefin copolymer composition, which comprises: norbornene units, in an amount of 75 wt.-% to 80 wt.-%, and Ethylene units, with a content of 20 wt.-% to 25 wt.-%. The contents are all based on the total weight of the cyclic olefin polymer composition (B).
13. The polypropylene composition according to claim 1, characterized in that, The cyclic olefin polymer composition (B) comprises at least one cyclic olefin copolymer, wherein the at least one cyclic olefin copolymer is selected from the group consisting of norbornene-ethylene copolymer and tetracyclododecene-ethylene copolymer or a blend of at least two of the cyclic olefin copolymers.
14. The polypropylene composition according to claim 1, characterized in that, The cyclic olefin polymer composition (B) comprises at least a first cyclic olefin polymer (b1) and a second cyclic olefin polymer (b2).
15. The polypropylene composition according to claim 1, characterized in that, The cyclic olefin polymer composition (B) comprises at least a first cyclic olefin polymer (b1) and a second cyclic olefin polymer (b2). The first cyclic olefin polymer (b1) has a glass transition temperature of less than 140°C as measured according to ISO 11357, and the second cyclic olefin polymer (b2) has a glass transition temperature of at least 155°C as measured according to ISO 11357.
16. The polypropylene composition according to claim 1, characterized in that, The highly isotropic propylene homopolymer (A) has at least one of the following characteristics: use 13 The content of isosteric five-unit fractions measured by 1C NMR ranged from 92% to 99.5%. According to ISO 1133, the MFR2 (2.16 kg / 230 °C) is 0.4 g / 10 min to 10 g / 10 min. The ash content, as measured according to ISO 3451-1 (1997), is 60 ppm or less. The crystallization temperature (Tc) measured according to ISO 11357 is 110°C to 130°C.
17. The polypropylene composition according to claim 1, characterized in that, The highly isotropic propylene homopolymer (A) has at least one of the following characteristics: use 13 The content of isosteric five-unit fractions measured by 1C NMR ranged from 96% to 98.5%. According to ISO 1133, the MFR2 (2.16 kg / 230 °C) is 0.5 g / 10 min to 5 g / 10 min. The ash content, as measured according to ISO 3451-1 (1997), is 30 ppm or less. The crystallization temperature (Tc) measured according to ISO 11357 is 110°C to 120°C.
18. A membrane comprising the polypropylene composition according to any one of claims 1 to 17.
19. The membrane according to claim 18, characterized in that, The membrane has a density of less than 6.0-10. -15 The conductivity is measured in S / cm, where the conductivity is obtained by dielectric impedance spectroscopy at 130°C using a 10-saturation method. -2 Alternating current at a frequency of Hz was measured on a film with a thickness of 100 μm.
20. The membrane according to claim 18, characterized in that, The membrane has a temperature of 3.0-10. -17 S / cm to below 3.0•10 -16 Conductivity in the range of S / cm, where conductivity was measured by dielectric impedance spectroscopy at 130°C using 10... -2 Alternating current at a frequency of Hz was measured on a film with a thickness of 100 μm.
21. The membrane according to any one of claims 18 and 19, characterized in that, Atomic force microscopy was used to examine a 10 × 10 μm section of a 300 μm thick film. 2 Visual inspection of the slices determined that the average diameter of the domains in the cyclic olefin polymer composition (B) was less than 2.0 μm.
22. A biaxially oriented film comprising a polypropylene composition according to any one of claims 1 to 17.
23. A capacitor comprising the biaxially oriented film according to claim 22.
24. A polypropylene composition, characterized in that, include: Based on 74.75 wt.-% to 90 wt.-% of the total weight of the polypropylene composition, of highly isotactic propylene homopolymer (A). Based on 5 wt.-% to 25 wt.-% of the total weight of the polypropylene composition, and a cyclic olefin polymer composition (B), and Based on the total weight of the polypropylene composition, 0.25 wt.-% to 2 wt.-% of random propylene copolymer solubilizer (C) is added.
Citation Information
Patent Citations
Polypropylene composition and preparation method thereof
CN101724195A
Process and apparatus for preparing propylene homopolymers and copolymers
EP0887379A1
Polypropylene composition for capacitor film
EP2995641A1
Multi-stage process for producing polyethylene
WO1992012182A1
Process for preparing polypropylene
WO1999024478A1
